2016
DOI: 10.1016/j.neulet.2016.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal administration of rapamycin inhibits the phosphorylation of DRG Nav1.8 and attenuates STZ-induced painful diabetic neuropathy in rats

Abstract: The mammalian target of rapamycin (mTOR) is a key regulator of mRNA translation and protein synthesis, and it is specifically inhibited by rapamycin. In chronic pain conditions, mTOR-mediated local protein synthesis is crucial for neuronal hyperexcitability and synaptic plasticity. The tetrodotoxin-resistant (TTX-R) sodium channel Nav1.8 plays a major role in action potential initiation and propagation and cellular excitability in DRG (dorsal root ganglion) neurons. In this study, we investigated if mTOR modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Previous trail has reported that the protein expression of Na v 1.8 in DRGs was decreased in PDN rats [25]. However, there was no significant changes of Na v 1.8 expression were detected in our experiment, which was consistent with some other experiments [26,27]. Although the importance of Nav1.9 in painful process was gradually confirmed, most studies of PDN have not mentioned too much.…”
Section: Discussionsupporting
confidence: 90%
“…Previous trail has reported that the protein expression of Na v 1.8 in DRGs was decreased in PDN rats [25]. However, there was no significant changes of Na v 1.8 expression were detected in our experiment, which was consistent with some other experiments [26,27]. Although the importance of Nav1.9 in painful process was gradually confirmed, most studies of PDN have not mentioned too much.…”
Section: Discussionsupporting
confidence: 90%
“…Then, eight rats were randomly chosen and designated as N group, and the rest were intraperitoneally administered 60 mg/kg of STZ with 0.1 mol/L sodium citrate solution (pH 4.50). 17 19 The blood glucose levels of all the rats, except N group, were measured at 72 hours after STZ injection (first experimental day). Only the rats with a blood glucose concentration higher than 13.8 mmol/L were chosen as model rats and used further in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Several lines of evidence have demonstrated that the AMPK and mTOR systems are also closely related with nociception. For example, the expression of mTOR protein in DRG or the spinal cord are altered in several types pain models such as neuropathic pain (Zhang et al 2013 ; Cui et al 2014 ), diabetic neuropathy (He et al 2016 ), and inflammation-induced pain (Asante et al 2009 ; Xu et al 2011 ) models. In addition, the activation of AMPK signal in general reduces nociception, allodynia or hyperalgesia observed in several types of pain models (Russe et al 2013 ; Ma et al 2015 ; Song et al 2015 ; Hasanvand et al 2016 ), suggesting that AMPK is an ultimate target molecules for relieving pain (Melemedjian et al 2011 ; Asiedu et al 2016 ; Price et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%